2006
DOI: 10.1002/chem.200500419
|View full text |Cite
|
Sign up to set email alerts
|

[Ru(TAP)3]2+‐Photosensitized DNA Cleavage Studied by Atomic Force Microscopy and Gel Electrophoresis: A Comparative Study

Abstract: Topological modifications of plasmid DNA adsorbed on a variety of surfaces were investigated by using atomic force microscopy (AFM). On mica modified with 3-aminopropyltriethoxysilane (APS) or poly-L-lysine, the interaction between the plasmid DNA and the surface "freezes" the plasmid DNA conformation deposited from solution, and the AFM images resemble the projection of the three-dimensional conformation of the plasmid DNA in solution. Modified mica with low concentrations of Mg(2+) leads to a decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Considering the structure of the complex, the most possible binding mode is the hydrogen bonds formed between the guanine residue on the intercalative ligand appo and GC base pairs of DNA. [53,[56][57][58].…”
Section: Luminescence Spectramentioning
confidence: 98%
“…Considering the structure of the complex, the most possible binding mode is the hydrogen bonds formed between the guanine residue on the intercalative ligand appo and GC base pairs of DNA. [53,[56][57][58].…”
Section: Luminescence Spectramentioning
confidence: 98%
“…We previously demonstrated that Ru II complexes containing at least two π-deficient polyazaaromatic ligands such as tap (1,4,5,8-tetraazaphenanthrene) are able to form a photoadduct on the guanine (G) base of DNA or ODN and can also photocleave plasmidic DNA. [13,14] These reactions are induced by a photoelectron transfer process from the G base to the excited complex. [15] We have shown that formation of the photoadduct could be targeted towards a G residue of a specific sequence by using ODNs conjugated with the [Ru(tap) 2 …”
Section: Introductionmentioning
confidence: 99%
“…For this, longer DNA sequences have to be used; therefore, 500-base-pair DNA restriction fragments and plasmid DNA pUC19 have been examined. It was shown a long time ago that the illumination of Ru-TAP complexes in the presence of plasmids (figure 8) induces cleavages, as revealed by the occurrence of open circular and linear forms of the plasmid from agarose electrophoresis analysis [53] and from atomic force microscopy detections [54]. It is well known that the coiled circular plasmid is transformed, just by one single nick, into its open circular form.…”
Section: Applications For Bi-adduct Formation With Two Absorbed Photomentioning
confidence: 99%